CompTIA Security+ (SY0-601) Cert Prep: 2 Secure Code Design and Implementation. - Chapple, Mike (linkedin.com, 2020)
Learn about the risks associated with application vulnerabilities—and the secure coding practices that can help you avoid attacks—as you prepare for the Security+ exam.